Die openbaringsleer van Schilder - A. L. A. Buys; S. A. Strauss (Acta Theologica)
Although Schilder’s theology was almost exclusively known in the Netherlands, its significance is not restricted to that country. In principle Schilder based his theology on revelation in Scriptures. According to Schilder, revelation may be described as God’s disclosing of the truth from heaven to people on earth in Jesus Christ. This revelation is embodied in various dispensations but always remains anthropomorphic, due to the love of God, which culminates in the Word becoming flesh. Two fundamental axioms of Schilder’s theology, namely the unity of Scriptures and the unity of the church can be derived from his firm belief in the unity of God. Schilder’s view on revelation is still relevant, because it provides an effective answer to both mysticism and fundamentalism.